A Randomized Clinical Trial of Oxytocin or Galantamine in Schizophrenia: Assessing the Impact on Behavioral, Lexical, and Self-Report Indicators of Social Affiliation. Issue 1 (3rd August 2020) - Dwyer, Kristen R; Andrea, Alexandra M; Savage, Christina L G; Orth, Ryan D; Shan, LeeAnn; Strauss, Gregory P; Adams, Heather A; Kelly, Deanna L; Weiner, Elaine; Gold, James M; McMahon, Robert P; Carpenter, William T; et al.
Abstract: Prior studies examining the impact of oxytocin on negative symptoms in schizophrenia have yielded mixed results. The current study explored whether oxytocin can improve more proximal indicators of social affiliation as indicated by changes in behavior, language and subjective indices of social affiliation among individuals with schizophrenia spectrum disorders during a role-play designed to elicit affiliative responses. We tested the hypothesis that daily intranasal oxytocin administered for 6 weeks would improve social affiliation as manifested by increased social skill ratings, use of positive, affiliative, and social words, and subjective responses from a previously published randomized controlled trial. Forty outpatients with schizophrenia or schizoaffective disorder were randomized to the oxytocin, galantamine, or placebo group and completed affiliative role-plays and self-report questionnaires of affect, reactions to the affiliative confederate, and willingness to interact at baseline and post-treatment. Results demonstrated that oxytocin was not effective at improving behavioral or subjective indicators of social affiliation. This study adds to a growing literature that the prosocial effects of oxytocin in schizophrenia are limited or null.